Coleoptera in amber from Cretaceous resiniferous forests. (September 2020) - Peris, David
Abstract: In the world of insects, beetles rule. Evolutionary and palaeoecological interpretations using fossil beetles from Cretaceous ambers have become increasingly frequent in recent years, consequently leading to the discovery of an increasing number of new coleopteran species. By the end of 2019, a total of 364 new species from 81 families (some of them only known as fossils) were compiled, which are presented in this article. Beetles are currently among the most important pollinators of basal flowering plants and are thought to have been so since the origin of angiosperms. Some recent studies on specimens from Cretaceous amber support this idea, indicating the existence of a pre-existing guild of beetles that pollinated gymnosperms during the Early Cretaceous, with some groups moving from older gymnosperm to more recent angiosperm hosts. The effect of wood-boring beetle pests on resiniferous ancient forests has been widely cited in the literature, but there is no direct evidence in Cretaceous ambers. The current abundance of Lymexylidae beetles in Kachin amber (Myanmar) suggests that together with abiotic factors such as wildfires, storms, hurricanes and volcanos, fungal infections should also be thoroughly analysed as a cause of resin release in the past. In this review, we show how beetles from Cretaceous ambers are a useful tool for studying community and trophic structures as well as evolutionary implications for the ecosystem. Highlights: Studies of fossil beetles from Cretaceous ambers have become frequent in recent years. By the end of 2019, a total of 364 new species from 81 families were compiled. The study of beetles from amber show evolutionary implications for the ecosystem. Beetles were about the earliest pollinators of angiosperms during the Cretaceous. Fungal infections should be analysed as a cause of resin release in the past.